CHARACTERIZATION OF ASPHALT MODIFICATION USING GROUND RUBBER AND REACTIVE RUBBER NR-g-MA AS COMPATIBILIZER - Ritonga , Winsyahputra; Humaidi, Syahrul; ., Motlan; ., Eddiyanto; Frida, Erna; Manurung, Posman (International Journal of Membrane Science and Technology, 2023)
This study aims to improve the quality of asphalt by adding ground tyre rubber (GR) and reactive rubber (NR-g-MA) as compatibilizers of asphalt-rubber mixability. The use of GR has been widely used to improve the performance of asphalt and extend the service life of asphalt. The NR-g-MA used was the product of the copolymerization of SIR-20 rubber grafts with maleic anhydrous (MA) through a melting process in an internal mixer. Mixing of GR in asphalt was carried out in an external mixer with composition of asphalt/GR 95/5 phr at the temperature of 180oC for 90 minutes. The performance of asphalts were measured based on conventional test of penetration and softening point. The rheological properties of asphalt were measured using a Dynamic Shear Rheometer (DSR). Important parameters of the rheological properties measured are complex shear modulus (G*) and phase angle (d). Asphalt resistance to the permanent deformation (rutting) were determined on asphalt that has undergone a short-term aging process in a rolling thin film oven (RTFO) and measured at high temperatures (58-82OC). Fatigue crack resistance was tested on asphalt that has undergone a long-term aging process using the method of pressure aging vessel (PAV) and measured at low temperatures (25-31OC). Asphalt-GR mixtures' chemical, thermal and morphological properties were studied using ATR-FTIR, DSC/TGA, and SEM respectively. The results showed that adding used ground rubber (GR) decreased the penetration value by 9.93 – 18.87% and increased the softening point of asphalt from 5.57 – 11.40%. Rheological analysis showed that the addition of GR and compatibilizer NR-g-MA increase the value of complex shear modulus (G*) and decrease the phase angle (d) of the asphalt. The addition of ground rubber and reactive rubber of NR-g-MA to asphalt improve the performance of asphalt because it has rutting resistance at high temperatures as well as improves asphalt cracking resistance at low-temperature measurements. The addition of NR-g-MA reactive rubber to modified asphalt ground rubber can increase the mixability of asphalt-rubber used tires.